Memristor-based arbiter Physically Unclonable Function (APUF) with multiple response bits - Loong J.T.H.; Nor Hashim N.A.; Hamid F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Delay circuits; Flip flop circuits; Aliasing; Applied voltages; Average values; Circuit size; D flip flops; Memristor; Multiple response; Physically unclonable functions; Memristors